2019
DOI: 10.1007/s13659-019-00224-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin Derivatives from Gastrodia elata

Abstract: Nine new gastrodin derivatives, including seven p-hydroxybenzyl-modified gastrodin ethers (1-7), 6′-O-acetylgastrodin (8), and 4-[α-d-glucopyranosyl-(1 →6)-β-d-glucopyranosyloxy]benzyl alcohol (9), together with seven known derivatives, were isolated from an aqueous extract of Gastrodia elata ("tian ma") rhizomes. Their structures were determined by spectroscopic and chemical methods as well as single crystal X-ray diffraction. Compounds 1-4, 7, 10, and 11 were also isolated from a reaction mixture by refluxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…To confirm the chemical reactions during processing and decocting of the herbal medicine [ 80 ], the fresh G. elata rhizomes were collected at the same field of “tian ma” (the steamed and dried rhizomes) and the extracts were prepared by sonicating of the fresh G. elata rhizomes and “tian ma” in H 2 O, MeOH, and EtOH for 0.5 h, respectively, followed by refluxing (sampling time: 0.5 h, 1.0 h, 1.5 h, 2.0 h, 4.0 h, and 6.0 h). The extract samples were analyzed by UPLC-HRESIMS using the aforementioned pure compounds as the references, showed that the composition and relative content of the extracts were varied with the extracting solvent and refluxing time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the chemical reactions during processing and decocting of the herbal medicine [ 80 ], the fresh G. elata rhizomes were collected at the same field of “tian ma” (the steamed and dried rhizomes) and the extracts were prepared by sonicating of the fresh G. elata rhizomes and “tian ma” in H 2 O, MeOH, and EtOH for 0.5 h, respectively, followed by refluxing (sampling time: 0.5 h, 1.0 h, 1.5 h, 2.0 h, 4.0 h, and 6.0 h). The extract samples were analyzed by UPLC-HRESIMS using the aforementioned pure compounds as the references, showed that the composition and relative content of the extracts were varied with the extracting solvent and refluxing time.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we reported 27 new and 40 known chemical constituents of the aqueous extract, along with their bioassays and pharmacological activities [ 71 – 79 ]. Especially we found that several p -hydroxybenzyl-modified gastrodins from the extract could be produced from a coupling reaction of the co-occurring p -hydroxybenzyl alcohol and gastrodin in H 2 O under refluxing [ 80 ]. This unraveled production of the new components during processing and decocting of “tian ma” in the classical application protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several Armillaria species with low pathogenicity, such as A. gallica, A. cepistipes, A. gallica, and A. nipponica, can be associated with G. elata (Guo et al, 2016) or Cyrtosia septentrionalis (Umata et al, 2013) as their primary nutrient provider. In addition, A. gallica has been successfully isolated, identi ed, and used for cultivation of G. elata for more than 50 years (Xu et al, 1989;Zhou, 1981). Given that these Armillaria fungi can be arti cially cultured and the symbiosis between G. elata and Armillaria can form under lab and eld conditions, such G. elata-Armillaria interaction systems provide exceptional opportunities to investigate the molecular mechanisms underlying mycoheterotrophic plant-fungus interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrodia elata Bl. is a widespread orchid that contains gastrodin, vanillanol, and other medicinal ingredients that play important roles in lowering blood pressure, increasing blood flow of the heart and brain, decreasing inflammation, and improving body immunity [ 2 , 3 ]. Lacking roots and leaves, Gastrodia elata is heterotrophic and depends on the symbiotic fungi Mycena spp.…”
Section: Introductionmentioning
confidence: 99%